Coleophora elea Baldizzone & Huemer, new species of the Coleophora oriolella Zeller, 1849 species-group (Lepidoptera, Coleophoridae) - Baldizzone, Giorgio; Huemer, Peter (Zootaxa, 2024)
Coleophora elea Baldizzone & Huemer, sp. nov., is described based on specimens collected from the Peloponnese peninsula (Greece). This species is closely related to C. oriolella Zeller, 1849, but it differs in external appearance and in characters of the male and female genitalia. Additionally, the two species are genetically distinct as evidenced by a p-distance of approximately 4% between their DNA barcodes (cytochrome c-oxidase subunit 1). Adult specimens and the genitalia of both species are illustrated for comparative purposes.